The war that saved my life - Bradley, Kimberly Brubaker (New York : Dial Books for Young Readers, 2015)
A young disabled girl and her brother are evacuated from London to the English countryside during World War II, where they find life to be much sweeter away from their abusive mother.
School Library Journal, November 2014.
Horn Book Starred, January 2015.
Pub Weekly, October 2014.
Kirkus Starred, October 2014.
Booklist, December 2014.
Horn Book, October 2015.
Keywords: World War, 1939-1945 -- Evacuation of civilians -- Great Britain -- Juvenile fiction; People with disabilities -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; World War, 1939-1945 -- Evacuation of civilians -- Fiction; People with disabilities -- Fiction; Brothers and sisters -- Fiction; World War, 1939-1945 -- Evacuation of civilians -- Fiction; People with disabilities -- Fiction; Great Britain -- History -- George VI, 1936-1952 -- Fiction